2022
DOI: 10.3389/fbioe.2022.820196
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Weight-Bearing on Tibiofemoral, Patellofemoral, and Patellar Tendon Kinematics in Older Adults

Abstract: Quantification of natural knee kinematics is essential for the assessment of joint function in the diagnosis of pathologies. Combined measurements of tibiofemoral and patellofemoral joint kinematics are necessary because knee pathologies, such as progression of osteoarthritis and patellar instability, are a frequent concern in both articulations. Combined measurement of tibiofemoral and patellofemoral kinematics also enables calculation of important quantities, specifically patellar tendon angle, which partly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…Next to muscle contraction, weightbearing also has an effect on patellofemoral kinematics. 16,17,23 Yet, our length change patterns largely correspond with a recent study investigating MPFL length changes during a weightbearing lunge motion, also demonstrating a decrease in MPFL length during early flexion. 18 This finding may conceivably indicate that the importance of active weightbearing relative to active nonweightbearing knee motion may be secondary for the assessment of MPFL length changes compared with interindividual variability.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Next to muscle contraction, weightbearing also has an effect on patellofemoral kinematics. 16,17,23 Yet, our length change patterns largely correspond with a recent study investigating MPFL length changes during a weightbearing lunge motion, also demonstrating a decrease in MPFL length during early flexion. 18 This finding may conceivably indicate that the importance of active weightbearing relative to active nonweightbearing knee motion may be secondary for the assessment of MPFL length changes compared with interindividual variability.…”
Section: Discussionsupporting
confidence: 89%
“…Last, MPFL length changes were assessed during a nonweightbearing open-kinetic chain active flexion-extension-flexion movement, which might not be representative of different activities during daily life. 17 However, our approach is more realistic than that of previous studies examining changes in MPFL length during passive knee flexion. Notwithstanding these limitations, this study offers valuable insights into length changes of the native MPFL during knee flexion, which is essential to obtain a better understanding of MPFL reconstruction and its related complications.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that increased weight bearing changes knee kinematics and contact characteristics. 1 2 3) Both biomechanical and physiological mechanisms of TKAs are associated with the mechanical stresses that are related to osteoarthritis. 4 5) For patients with severe and advanced osteoarthritis, TKAs are the best treatment option.…”
mentioning
confidence: 99%